PERAN RASIO LIKUIDITAS TERHADAP EFISIENSI DAN EFEKTIVITAS OPERASIONAL BANK SYARIAH DAN BANK KONVENSIONAL - Wulan Ramadani Trisnaudy; Ersi Sisdianto (PT. Intelek Cendikiawan Nusantara, 2024)
Liquidity ratios play a strategic role in assessing the efficiency and effectiveness of bank operations, both in Islamic and conventional banks. This article highlights the importance of liquidity ratios as key indicators in liquidity management, emphasizing the different approaches of the two types of banks. Islamic banks rely on sharia principles that avoid interest and emphasize profit-sharing system, while conventional banks utilize the flexibility of interest-based instruments. Islamic banks show better liquidity stability despite being less flexible, while conventional banks are more adaptive but risk facing high costs. The study also highlights the unique challenges faced by Islamic banks, including the limitations of Shariah-based instruments, which may hinder liquidity efficiency. However, the risk-sharing system provides an advantage in maintaining fund stability. In contrast, conventional banks have the advantage of access to a wide range of money market instruments, which allows for faster response to market changes but at the consequence of higher operational costs. The analysis shows that innovation in liquidity management can be a solution to integrate the advantages of each system. This approach allows Islamic banks to improve competitiveness without compromising on sharia principles. By understanding these differences and opportunities, both types of banks are expected to contribute to overall financial stability. The findings provide new insights into how optimal liquidity ratio management can support sustainable growth in the banking sector.